The role of sulfonate groups and hydrogen bonding in the proton conductivity of two coordination networks - Javed, Ali; Steinke, Felix; Wöhlbrandt, Stephan; Bunzen, Hana; Stock, Norbert; Tiemann, Michael (Beilstein Journal of Nanotechnology, 2022)
The proton conductivity of two coordination networks, [Mg(H2O)2(H3L)]·H2O and [Pb2(HL)]·H2O (H5L = (H2O3PCH2)2-NCH2-C6H4-SO3H), is investigated by AC impedance spectroscopy. Both materials contain the same phosphonato-sulfonate linker molecule, but have clearly different crystal structures, which has a strong effect on proton conductivity. In the Mg-based coordination network, dangling sulfonate groups are part of an extended hydrogen bonding network, facilitating a “proton hopping” with low activation energy; the material shows a moderate proton conductivity. In the Pb-based metal-organic framework, in contrast, no extended hydrogen bonding occurs, as the sulfonate groups coordinate to Pb2+, without forming hydrogen bonds; the proton conductivity is much lower in this material.
Keywords: coordination network; coordination polymer; impedance spectroscopy; metal-organic framework; proton conductivity